A Comprehensive Insight on Adsorption of Polyaromatic Hydrocarbons, Chemical Oxygen Demand, Pharmaceuticals, and Chemical Dyes in Wastewaters Using Biowaste Carbonaceous Adsorbents - Khurshid, H. (Hindawi Limited, 2022)
Recent trends in adsorption of hazardous organic pollutants including Polyaromatic Hydrocarbons (PAHs), Chemical Oxygen Demand (COD), Pharmaceuticals, and Chemical Dyes in wastewater using carbonaceous materials such as activated carbon (AC) and biochar (BC) have been discussed in this paper. Utilization of biomass waste in the preparation of AC and BC has gained a lot of attention recently. This review outlines the techniques used for preparation, modification, characterization, and application of the above-mentioned materials in batch studies. The approaches towards understanding the adsorption mechanisms have also been discussed. It is observed that in the majority of the studies, high removal efficiencies were reported using biowaste adsorbents. Regarding the full potential of adsorption, varying values were obtained that are strongly influenced by the adsorbent preparation technique and adsorption method. In addition, most of the studies were concentrated on the kinetic, isotherm equilibrium, and thermodynamic aspects of adsorption, suggesting the dominant isotherm and kinetic models as Langmuir or Freundlich and pseudo-second-order models. Due to development in biosorbents, adsorption has been found to be increasingly economical. However, application of these adsorbents at commercial scale has not been adequately investigated and needs to be studied. Most of the studies have been conducted on synthetic solutions that do not completely represent the discharged effluents. This also needs attention in future studies. Â© 2022 Hifsa Khurshid et al.